Pro-inflammatory activation of monocytes in patients with immunoinflammatory rheumatic diseases - E. V. Gerasimova; I. G. Kirillova; M. V. Shalygina; T. V. Popkova (Медицинская иммунология, 2024)
The development of subclinical atherosclerosis in patients with rheumatoid arthritis (RA) is associated with chronic inflammation, one of the key mechanisms of which may be abnormal activation of macrophages.Objective: To assess the characteristics of pro-inflammatory activation of circulating monocytes in patients with early RA depending on the presence of subclinical atherosclerosis of the carotid arteries.The study included 60 patients (42 women and 18 men) with early RA without signs of cardiovascular disease. Atherosclerotic vascular disease was diagnosed by identifying carotid atherosclerotic plaques. Basal and stimulated monocyte lipolysaccharide (LPS) secretion was studied in initial monocyte cultures obtained by immunomagnetic separation from blood. Quantification of the cytokines TNFα and IL-1β was obtained in the culture fluid by ELISA. Proinflammatory activation of monocytes was calculated as the ratio of LPSstimulated and basal secretion.Atherosclerotic plaques of the carotid arteries were found in a third of RA patients; they were detected more often in men (50%) than in women (26%, p < 0.05). The carotid thickness of the intima media complex correlated with the level of total cholesterol (R = 0.20; p = 0.001) and ESR (R = 0.31; p = 0.03). In RA patients and subclinical carotid atherosclerosis, cultured blood monocytes demonstrated higher basal TNFα secretion (294.6 (185.3-778.2) vs 146.1 (27.9-79.9) pg/mL, p < 0.01) and low activation of TNFα (9.5±2.1 vs 19.8±3.9, p < 0.001) and IL-1β (6.1±2.3 vs 9.5±1.8, p = 0.03) compared with patients without lesions of the carotid arteries. In RA patients with carotid atherosclerotic plaques, a relationship was found between LPS-stimulated IL-1β secretion and the level of total blood cholesterol (R = 0.36, p = 0.01).Data were obtained on a more powerful inflammatory potential of peripheral blood monocytes in patients with early rheumatoid arthritis in the case of detection of the subclinical carotid atherosclerosis.